Capacited Vehicle Routing Problem with CO2 Emission Minimization Considering Path Slopes - P. Cantão, L. A.; Yamakami, A.; Cantão, R. F. (Trends in Computational and Applied Mathematics, 2022)
This work presents the application of a CO2 emission estimation function for cargo vehicles on a Capacited Vehicle Routing Problems (CVRP) setting, considering route’s slopes variation. Comparisons were established with functions minimizing fuel consumption and route length in a case study about selective collection of recyclable waste at Sorocaba, state of São Paulo, Brazil. Routes with lower emissions have been achieved without significantly increasing fuel consumption or distance traveled.